1221. Genetic Characteristics of Healthcare-Associated Methicillin-Resistant Staphylococcus aureus (HA-MRSA) Belonging to Clonal Complex 5 (CC5) in Latin-America. (26th November 2018) - Reyes, Jinnethe; Carvajal, Lina P; Rios, Rafael; Echeverri, Aura; Rincon, Sandra; Munita, Jose M; Tran, Truc; Panesso, Diana; Arias, Cesar; Diaz, Lorena
Abstract: Background: MRSA are responsible for a high proportion of healthcare-associated infections. HA-MRSA is multidrug resistant, and infections occur most frequently among inpatients, for example, those who have undergone invasive medical procedures or those aged 50 to 60 years and older. Dominance of multidrug-resistant CC5 (Chilean and New York/Japan clones) was prevalent in infections in Latin America with the notable exception of Colombia and Ecuador where USA300-LV isolates dominate. We performed genetic characterization of HA-MRSA-CC5 isolates recovered from infections in nine countries (12 hospitals). Methods: Species identification of S. aureus and presence of mecA were performed by PCR. We determined MICs to common anti-MRSA antibiotics and performed screening for VISA phenotype. Molecular characterization included detection of lukSF-PV and SCC mec typing. PFGE and MLST were performed in selected MRSA isolates with susceptibility patterns typical of the Chilean (ST5-MRSA-I) and USA300-LV (ST8-MRSA-IV) lineages. Results: A total of 665 S. aureus isolates were prospectively recovered from 592 patients. A high frequency of methicillin resistance (>40%) was observed in all countries (62%, 55%, 44%, and 40% in BRA, PER, CHI and ARG, respectively). Decreased susceptibility to VAN was not observed and VAN MIC90 was 1 µg/mL. In PER and CHI, the overwhelming majority of isolates (89%) belonged to the Chilean/Cordobes clone (CC5) with susceptibility patterns typical of this lineage (Resistance to β-lactams, MLSB-type, quinolones, and aminoglycosides). The New York/Japan clone (ST5-MRSA-II) was predominant in Brazil, replacing the prevalent hospital-associated Brazilian (ST239-MRSA-III) lineage. Most Argentinian MRSA isolates exhibiting a CA (ST5-IV) pattern, previously described in this country. Conclusion: A variety of MRSA genetic lineages are circulating in Latin America with geographic clustering and clonal replacement. Dissemination of the CA-USA300-LV has not occurred beyond the northern region of the subcontinent. Disclosures: J. M. Munita, Pfizer: Grant Investigator, Research grant. C. Arias, Merck & Co., Inc.: Grant Investigator, Research support. MeMed: Grant Investigator, Research support. Allergan: Grant Investigator, Research support.